Effect of BN/SiC interfacial coatings on the tensile properties of SiC/SiC minicomposites fabricated by PIP. Issue 16 (November 2020) - Dai, Jianwei; Wang, Yiguang; Xu, Zhenhua; Mu, Rende; Liu, Wei; He, Limin
Abstract: Boron nitride and silicon carbide interfacial coatings were deposited by chemical vapor infiltration to prepare SiC/SiC minicomposites by the precursor infiltration and pyrolysis process. The tensile properties of the SiC/SiC minicomposites were assessed by the acoustic emission method. A single-layered BN coating increased the strength of the uncoated minicomposite from 416.4 MPa to 478.6 MPa, while the strengths of the BN/SiC-1 and BN/SiC-2 samples with a double-layered coating were 582.3 and 638.1 MPa, respectively. The total thickness of the BN/SiC-2 coating was the same as that of BN/SiC-1, while the BN/SiC-2 sample had a thicker BN layer. Besides the release of residual stress and elastic deformation stages, the stress-strain curve of minicomposite with interfacial coating contains a non-linear stage corresponding to the matrix crack generation, propagation, and deflection. Moreover, minimal fiber debonding was observed in the uncoated minicomposite, whereas fiber debonding of BN and BN/SiC-1 minicomposites occurred at the interface between the BN coating and fibers. In the double-layered BN/SiC-2 minicomposites, following matrix crack generation and propagation into the BN coating, cracks deflected both between the sublayers and at the interface between BN and fibers, where the debonding occurred.